KUALITAS LAPORAN KEUANGAN DAN KEPERCAYAAN STAKEHOLDER (Studi Pada Satuan Kerja Wilayah Kerja KPPN Mataram) - Muhammad Naufal Arifin; Lillik Handajani; Alamsyah h (Master of Accounting Universitas Trunojoyo Madura, 2016)
This study is intended to examine empirically influence of competency of human resource, roles of internal auditor, application of SAP, implementation of IT, and SPI towards quality of financial statement. Furthermore, it also examines influence of trust of stakeholders, and roles of GGG as moderating variables. This research involves 53 organizational units of KPPN Mataram, which acquired WDP (qualified opinion) and TMP (disclaimer of opinion). Data is acquired through questionnaire. Findings of this study indicated that competency of human resources, application of IT and SPI affect positively towards quality of financial statements. Meanwhile, roles of internal auditor and implementation of SAP do not affect significantly. In addition, quality of financial statements affect trust of stakeholders, but GGG is not able to act as moderating variable between quality of financial statements and trust of stakeholders. Implication of this study is that quality of financial statement can be improved by enhancing competency of human resources as the first step of realization transparency and accountability of financial statement.